Sidewalk infrastructure assessment using a multicriteria methodology for maintenance planning - Sousa, Nuno (2018)
Sidewalks constitute the main guideway for the walking mode of transport and serve as a fundamental infrastructure for personal travel including commuting. This is because practically every motorized trip is preceded or concluded by nonmotorized travel. The assessment of sidewalk performance, in the sense of its suitability for walking, involves consideration of multiple aspects, whose precise treatment requires in turn the use of multicriteria methods to support decisions. This article proposes a multicriteria methodology for this purpose, thus setting the stage for a subsequent agency decision regarding maintenance strategy development. The methodology is based on a set of infrastructure attributes, directly intervenable by these authorities, and uses the ELECTRE TRI method to assign sidewalks under study to performance classes. It is practical to use and can be applied to any city, at any scale. The approach is thoroughly discussed, and demonstrated for a case study comprising several sidewalks in the city of Coimbra, Portugal. The results indicate that a considerable fraction of these sidewalks are in mediocre condition, and the multicriteria classifying methodology readily suggested intervention strategies, effectively aiding in the decision making.